In vitro antifungal activity of Rhazya stricta - Khan, Saifullah (PubMed, 2007)
Rhazya stricta is a small glabrous shrub, widely distributed throughout Western Asia from Yemen to Arabia, to the North West Province of India and abundantly found in various regions of Pakistan. Larvicidal and antifungal studies of polar and non polar aerial parts extracts of Rhazya stricta were performed using brine shrimps larvae for larvicidal study and for antifungal study microorganisms, Trichophyton longifusis, Aspergillus flavus, Candida albicans, Microsporum canis and Fusarium solani were used respectively. The methanol fraction showed significant cytotoxicity with LC50 17.809 microg/ml, having mortality rate 73.33% at highest dose. While pet-ether, chloroform and carbon tetrachloride possessed moderate to low cytotoxicity with their LC50 values 49.077 microg/ml, 95.859 microg/ml and 80.489 microg/ml respectively, ethyl acetate fraction showed no cytotoxicity. Results of antifungal studies showed that fractionated samples of methanol and chloroform possessed significant antifungal activities against, Trichophyton longifusis, Aspergillus flavus, Candida albicans and Fusarium solani respectively. Due to these promising results, further in vivo studies over R. stricta must be conducted.